Nationwide use of REBOA in adolescent trauma patients: An analysis of the AAST AORTA registry. Issue 11 (November 2020) - Theodorou, Christina M.; Brenner, Megan; Morrison, Jonathan J.; Scalea, Thomas M.; Moore, Laura J.; Cannon, Jeremy; Seamon, Mark; DuBose, Joseph J.; Galante, Joseph M.; ,
Highlights: This study evaluated the current use of Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) in patients under 18 years old in the U.S. Eleven pediatric trauma patients have undergone REBOA placement with a survival of 30%. Pediatric trauma patients who had REBOA placed had a significant increase in their systolic blood pressure. Abstract: Background: Trauma is the leading cause of death for children and adolescents. Resuscitative endovascular balloon occlusion of the aorta (REBOA) is a minimally invasive method of hemorrhage control used primarily in adults. We aimed to characterize REBOA use in pediatric patients. Methods: The American Association for the Surgery of Trauma (AAST) Aortic Occlusion for Resuscitation in Trauma and Acute Care Surgery (AORTA) registry was queried for patients <18 years old undergoing REBOA placement (2013-2020). The primary outcome was mortality. Secondary outcomes included injury severity score (ISS), additional interventions, and complications. Results: Eleven patients with a median age of 17 years old had REBOA placed, with a survival rate of 30%. Inflation of the REBOA balloon resulted in a significant increase in systolic blood pressure (SBP) (median SBP pre-REBOA 53 mmHg vs. post-REBOA 110 mmHg, p=0.0007). Patients were severely injured with a median ISS of 29 (interquartile range 16-42). There were no access-site complications. All three surviving patients had a discharge Glasgow Coma Scale of 15. Conclusion: REBOA is used in patients <18 years old, but all reported patients in this registry were adolescents. No REBOA-related complications were reported. Identifying pediatric patients who may benefit from REBOA and modifying currently existing technology for this group of patients is an area of ongoing research.